New Findings Regarding the Thermal Oxidation and Biomimetic Depositions on the Corrosion Resistance of the Ti-6Al-4V Alloy - Ribeiro Maestro, Carolina Aurélia; Santo Bueno , Alysson Helton; Marins Balestra, Roseli; de Sousa Malafaia , Artur Mariano; Moreto, Jeferson (Orbital: The Electronic Journal of Chemistry, 2022)
Our research group has been working on the surface functionalization of Ti-6Al-4V alloy by using thermal oxidation followed by CaP and Bi-CaP biomimetic depositions. In this short communication, we present new insights into the corrosion behaviour of the treated system by using potentiodynamic polarization tests. Our results demonstrated lower values of electric current density for the CaP specimens when compared to the Bi-CaP, indicating a tendency for the CaP samples to remake the passive film. Another reasonable explanation may be related to the displacement of CaP particles or the formation of corrosion products that partially block the pores of the coating. Morphological analyzes of all treated surfaces after the potentiodynamic polarization tests also suggest the improvement of the corrosion resistance of the Ti-6Al-4V alloy.